2003
DOI: 10.1210/jc.2002-021453
|View full text |Cite
|
Sign up to set email alerts
|

Association of Resistin Gene 3′-Untranslated Region +62G→A Polymorphism with Type 2 Diabetes and Hypertension in a Chinese Population

Abstract: Resistin, a recently discovered polypeptide, antagonizes insulin action and may play a part in the pathogenesis of insulin resistance. This study investigates whether resistin gene polymorphism can be associated with type 2 diabetes. We studied 1102 Chinese type 2 diabetes patients and 743 subjects without diabetes. The resistin 3'-untranslated region (UTR) +62G-->A polymorphism was determined by PCR. Type 2 diabetes subjects had a lower frequency of resistin gene 3'UTR +62A allele (GG:GA/AA, 83.5%:16.5%) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 34 publications
6
52
1
1
Order By: Relevance
“…Although SNPs in the promoter region of RETN have previously been associated with the circulating resistin level [21,23,25,29], only one previous study has demonstrated an association between resistin level and rs34861192 [29]; in that study, the number of participants was smaller than that in the present study. The rs3745368 polymorphism (also known as +62G→A) in the 3′ untranslated region of RETN has previously been associated with hypertension and type 2 diabetes [18,19,22]. , respectively (corrected by the Bonferroni method by multiplying the raw p values by 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SNPs in the promoter region of RETN have previously been associated with the circulating resistin level [21,23,25,29], only one previous study has demonstrated an association between resistin level and rs34861192 [29]; in that study, the number of participants was smaller than that in the present study. The rs3745368 polymorphism (also known as +62G→A) in the 3′ untranslated region of RETN has previously been associated with hypertension and type 2 diabetes [18,19,22]. , respectively (corrected by the Bonferroni method by multiplying the raw p values by 11).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated an association between increased serum resistin concentration and metabolic disorders, including obesity, insulin resistance, type 2 diabetes, hypertension, dyslipidaemia and atherosclerotic cardiovascular disease [9][10][11][12][13][14][15]. Moreover, polymorphisms of the human resistin gene (RETN) have also been found to be associated with such disorders [16][17][18][19][20][21][22][23][24][25]. However, not all studies have reproduced such findings [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Nevertheless, some genetic case-control studies have demonstrated that polymorphisms of the human resistin gene have been linked to insulin resistance in certain populations. [21][22][23] Moreover, resistin expression is positively correlated with insulin resistance in humans, 24,25 and serum resistin levels are elevated in human obesity 26 and type 2 diabetes. 17 The plasma concentrations of resistin in patients with insulin resistance remain to be carefully defined, although preliminary studies suggest that mean circulating resistin levels may be 40 ng/mL in diabetes (versus 15 ng/mL in lean nondiabetic patients).…”
Section: Discussionmentioning
confidence: 99%
“…We genotyped four previously identified non-coding SNPs: −420C>G (rs1862513) from the promoter region [12,13,14,15,17], +156C>T (rs3219177) [13,14,15,17,18,21] and +298G>A (rs3745367) [14,17,18,19] from intron 2, and +1084G>A (rs3745368) from the 3′ untranslated region (UTR) on exon 4 [16,21] of the resistin gene on chromosome 19. These four SNPs were chosen because they had shown evidence of association with Type 2 diabetes-related traits in other study samples [12,13,14,15,16]. The SNPs had an allele frequency of >0.1 in Caucasians, and comprised four of the six common (>0.1) variations identified in previous studies that screened both coding and regulatory regions of the gene for polymorphisms [13,14,15,17,18,20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Non-coding variants of the gene have been identified [12,13,14,15,16,17,18,19,20,21,22] and have been shown to be associated with variables related to weight [12,13], insulin [14,15] and blood pressure [16]. A recent study reported that a polymorphism in the promoter region was associated with resistin mRNA levels in abdominal subcutaneous fat [12].…”
Section: Methodsmentioning
confidence: 99%